Predictors of psychological distress and Coronavirus fears in the first recovery phase of the Coronavirus Disease 2019 pandemic in Germany - Biermann, Miriam; Vonderlin, Ruben; Mier, Daniela; Witthöft, Michael; Bailer, Josef (Frontiers in psychology, 2021)
Objectives: While previous research has mainly focused on the impact of the first acute phase of the COVID-19 pandemic on mental health, little empirical knowledge exists about depression, anxiety, and somatic symptom levels and possible predictors of symptom levels in the pandemic’s recovery phase. The present study aimed to analyze the mental burden of a convenience ample of the general German population during the first recovery phase of the pandemic and to identify significant predictors of symptom levels.Methods: Standardized measures of anxiety (GAD-2), depression (PHQ-2), somatic symptoms (PHQ-15), and health anxiety, as well as measures of COVID-19 fears and possible vulnerability factors, were administered through a national, cross-sectional online survey (n = 2160, mean age 42.7 years, 75% female), asking participants for their current symptom levels and their symptom levels prior to the COVID-19 pandemic.Results: Our findings show significantly elevated levels of depression, anxiety, somatic symptoms, and health anxiety in the recovery period compared to before the pandemic. The current prevalence rates based on self-reporting were 26.7% for depression, 24.5% for anxiety, and 29% for somatization. The strongest predictors of these symptom reports included domain-specific pre-existing symptom levels, neuroticism, biological COVID-19 risk factors, avoidance of illness information, and younger age. The most important predictors of COVID-19 fears were subjective COVID-19 risk perception, followed by pre-existing health anxiety, the number of biological COVID-19 risk factors, older age, neuroticism, avoidance of illness information and female gender.Discussion: These findings indicate the need for specific psychological programs to help individuals with enhanced psychological and biological vulnerability to cope better with the mental distress experienced during all phases of the ongoing COVID-19 crisis.
Gesehen am 02.03.2022